2013
DOI: 10.1002/pds.3424
|View full text |Cite
|
Sign up to set email alerts
|

Does antidepressant medication use affect persistence with diabetes medicines?

Abstract: The results of this large population-based study demonstrate that depression may be contributing to non-compliance with medicines for diabetes and highlight the need to provide additional services to support appropriate medicine use in those initiating diabetes medicines with co-morbid depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 24 publications
1
21
1
Order By: Relevance
“…Interventions specifically designed to improve medication adherence barriers in individuals at‐risk for poor adherence could lead to better clinical outcomes . For example, the observation from the present study that a higher CES‐D score could constitute a barrier for adherence is consistent with other studies . To target depression as a barrier to medication adherence for comorbid conditions, studies have analysed the extent to which integrated care could be effective in treating both disease outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interventions specifically designed to improve medication adherence barriers in individuals at‐risk for poor adherence could lead to better clinical outcomes . For example, the observation from the present study that a higher CES‐D score could constitute a barrier for adherence is consistent with other studies . To target depression as a barrier to medication adherence for comorbid conditions, studies have analysed the extent to which integrated care could be effective in treating both disease outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…6,15 For example, the observation from the present study that a higher CES-D score could constitute a barrier for adherence is consistent with other studies. 12,[34][35][36][37][38][39] To target depression as a barrier to medication adherence for comorbid conditions, studies have analysed the extent to which integrated care could be effective in treating both disease outcomes. A randomised trial in 64 individuals with hypertension and depression showed that integrated care, focused on treating hypertension and depression simultaneously, improved adherence to antihypertensive medications and resulted in lower blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Depression and respiratory disease were the most prevalent unrelated comorbid conditions in the present study, and both can affect diabetes management and health outcomes . Depression in patients with diabetes is associated with decreased medication persistence, poorer disease control and, as a result, increased diabetes complications, hospitalizations and higher healthcare costs . The use of high‐dose corticosteroids in people with diabetes and comorbid respiratory disease is associated with a 94% (hazard ratio 1.94, 95% CI 1.14–3.28) increased risk of diabetes‐hospitalization .…”
Section: Discussionmentioning
confidence: 99%
“…As the sole payer of these health services, the DVA maintains custodianship over a wide variety of routine data collections including dispensing and medical service claims and hospitalisations. Not surprisingly, the vast majority of studies using individual‐level data with linkages to other health datasets are based on this subset of elderly Australians . However, the DVA client population is small (approximately 220 000 veterans and their dependents with health care entitlements across Australia in 2014) and therefore of insufficient size to power a broad range of comparative effectiveness and safety evaluations…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, the vast majority of studies using individual-level data with linkages to other health datasets are based on this subset of elderly Australians. [23][24][25][26][27] However, the DVA client population is small (approximately 220 000 veterans and their dependents with health care entitlements across Australia in 2014) and therefore of insufficient size to power a broad range of comparative effectiveness and safety evaluations. 28 While we applaud the DVA for their continued research support, there has been a strong push to extend linkage between PBS claims and other collections to undertake pharmacoepidemiological research in the wider Australian population.…”
Section: Discussionmentioning
confidence: 99%